(untitled) (Sociología y tecnociencia, 2021)
It would be an understatement to describe 2020 as the challenging year. Coronavirus swept the globe and over 2.16 million people have died from the disease till-date. Even in Southeast Asia, which has fared moderately well in minimalizing deaths, economies of these countries have either ground to the halt or profoundly slender due to the region’s dependance on tourism and export. In this wake, many research institutions have been working to analyze the impact, aftereffects, and ways to limit the spread of Covid-19. But what have South-east Asia learnt from nearly a one year of responses to COVID-19? A key question, not yet answered, is how to find the elusive balance between economic curbs, public health concerns and attain the right balance between open borders and rigorous safety measures.